Denmark : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper analyzes household balance sheet structure in Denmark and sensitivity to rising rates. Households in Denmark have gotten considerably wealthier in recent decades. High household assets, in particular in the mandatory pension system and housing, provide stability by funding future consumption and protecting against shocks. The high, but mostly illiquid, assets have a counterpart, however, in the high household debt, as households often need to borrow to consume or buy property. The resulting combination of large assets and liabilities on household balance sheets make the Danish economy sensitive to interest-rate changes. Sudden increases in interest rates can create macroeconomic instability via their impact on the debt service of households and knock-on effects on consumption.